What are British Professional Perceptions of Disordered Eating amongst British Pakistani Adolescents? - Choudhry, Nageena (2014)
Abstract The aim of this paper is to explore the under representation of eating disorders in British Pakistani Adolescents. This was carried out by interviewing British professionals and investigating contributing factors that may hinder British Pakistani adolescent females accessing services for eating disorders. A qualitative methodology was used to gain in-depth understandings of the data. Semi-structured interviews were carried out with a sample group of four British professionals with experience of working with adolescents with eating disorders. The findings from the research suggest there are similarities in the contributing factors influencing the development of eating disorders in British Pakistani adolescents and Caucasian adolescents. However, research findings also suggest low uptake of specialist services as a result of cultural and other issues, making accessing support difficult when compared with Caucasian adolescents. Finally, clinical implications are discussed and suggestions for future research are proposed.